АДАБИЁТЛАРНИНГ ЎЗАРО АЛОҚАДОРЛИГИ ВА БИР-БИРИГА ТАЪСИРИ - Алдашева, Ш.Ж. (SCIENCE and SOCIETY, 2021)
The article argues that the interconnectedness and interaction of literature is an important factor in the development of artistic creativity, which can have a positive effect only if it is predominantly creative, that is, innovative.